المسؤولية المدنية للمصرف عن الاخلال بقواعد الاستعلام المصرفي - امين, خالص نافع; حسين, صفا علي (Journal of Legal Sciences, 2019)
As a result of the important role played by the banks as institutions contribution and effective in the management of economic activity,they are committed through the operations and activities of the queries for clients, and this is what makes them has extensive information about their customers of their activities, as well as information concerning its terms require success in this the role to be decisions catchment for safety features and precautions taken to avoid caffeine what faced the risk of, and be a distinctive destination for customers and businessmen who are trying to get the financial and banking information held by. But the breach makes the bank civilians responsible for the damages sustained by the customer or third party, it must to this commitment be matched by responsibility materialize as a result of its breach, even if it seems contradictory that both pour in the same direction, namely improving the level of the Bank's performance when the query, and achieve interest to the other party which is committed to him the bank, as well as to ensure the interests of both sides. Whenever it increased legal protection and of responsibility, the greater the commitment that has imposed such protection force, and without the commitment does not become any usefulness